Recurring Colonial Ignorance: A Genealogy of the Swedish Energy System - Össbo, Åsa (Journal of Northern Studies, 2019)
This chapter sketches a genealogy of the backbone of the Swedish energy system—hydroelectricity, starting with the recent state investigation on Water Activities and its version of history that stands in contrast to research showing the historical as well as present-day colonialism manifested in Swedish policy on hydropower development in Sápmi and the apparent exclusionary practice of only inviting certain stakeholders to participate in the investigation, none of whom represented Sami organisations or institutions. In order to trace the formation of this practice, a lineage is established through a study of the uncharted judicial and political impacts of an exemption act facilitating hydroelectric power extraction during the Second World War, an act that eventually became conventional law. After the war, Swedish hydropower expansion was mainly pursued in the northern parts of the country, which coincide with Sápmi—the traditional land of the Indigenous Sami people. Sweden’s environmental policies of today are focused on what is perceived as renewable and sustainable energy sources. While leaning heavily on hydropower, these policies rarely acknowledge the consequences of hydropower extraction in Sápmi. Nor are the traces of water rights left in the terrain recognised, traces that make possible a recurring colonial practice of ignorance among present-day Swedish decision makers.